2015
DOI: 10.3354/meps11078
|View full text |Cite
|
Sign up to set email alerts
|

Size matters at deep-sea hydrothermal vents: different diversity and habitat fidelity patterns of meio- and macrofauna

Abstract: Species with markedly different sizes interact when sharing the same habitat. Unravelling mechanisms that control diversity thus requires consideration of a range of size classes. We compared patterns of diversity and community structure for meio- and macrofaunal communities sampled along a gradient of environmental stress at deep-sea hydrothermal vents on the East Pacific Rise (9° 50′ N) and neighboring basalt habitats. Both meio- and macrofaunal species richnesses were lowest in the high-stress vent habitat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 54 publications
3
60
0
Order By: Relevance
“…Tubeworms were dissected and incubated aboard the ship. To follow the symbiont escape process, we used custom-designed symbiont recruitment plates equipped with glass coverslips in high-pressure vessels to simulate deep-sea conditions of bottom water with 175 μmol·L −1 oxygen (65) and about 2-3°C at the basalt surfaces in the axial summit trough of the EPR (68). Pressure vessels for the simulated deep-sea treatments were filled with 0.2 μm sterile-filtered seawater and kept at 4°C without flow and 171.6 ± 0.…”
Section: Discussionmentioning
confidence: 99%
“…Tubeworms were dissected and incubated aboard the ship. To follow the symbiont escape process, we used custom-designed symbiont recruitment plates equipped with glass coverslips in high-pressure vessels to simulate deep-sea conditions of bottom water with 175 μmol·L −1 oxygen (65) and about 2-3°C at the basalt surfaces in the axial summit trough of the EPR (68). Pressure vessels for the simulated deep-sea treatments were filled with 0.2 μm sterile-filtered seawater and kept at 4°C without flow and 171.6 ± 0.…”
Section: Discussionmentioning
confidence: 99%
“…Species richness is inversely correlated with the intensity of vent fluid emissions (Gollner et al 2010b. In their recent study, Gollner et al (2015) showed that, unlike the majority of macrofaunal species, meiofaunal species were distributed across proximate and distant basalt habitats and were, thus, not restricted to vent habitats.…”
Section: Meiofauna From Hydrothermal Ventsmentioning
confidence: 99%
“…Hydrothermal sediments have also been suggested to act as evolutionary bridges between hard substratum vents and methane seeps (Kiel, 2016). To utilise in situ production in hydrothermal sediments, fauna must overcome the environmental stress associated with hightemperature, acidic, and toxic conditions Gollner et al, 2015). The combination of elevated toxicity and in situ organic matter (OM) production results in a different complement of ecological niches between hydrothermal and background conditions that elicits compositional changes along a productivity-toxicity gradient (Bernardino et al, 2012;Gollner et al, 2015;Bell et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…To utilise in situ production in hydrothermal sediments, fauna must overcome the environmental stress associated with hightemperature, acidic, and toxic conditions Gollner et al, 2015). The combination of elevated toxicity and in situ organic matter (OM) production results in a different complement of ecological niches between hydrothermal and background conditions that elicits compositional changes along a productivity-toxicity gradient (Bernardino et al, 2012;Gollner et al, 2015;Bell et al, 2016b). Hydrothermal sediments offer different relative abundances of chemosynthetic and photosynthetic organic matter, depending upon the supply of surface-derived primary productiv-ity and levels of hydrothermal activity (Tarasov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%